COMPARATIVE ANALYSIS OF YEOH, OGDEN, ARRUDA-BOYCE HYPERELASTIC CONSTITUTIVE MODEL AND SIMPLE RHEOLOGICAL MODEL OF PT CIPTA DAYA MANDIRIINSANI INDONESIA‟S INDUSTRIAL RUBBER - (NIM : 13106116); Tim Pembimbing : Dr. Ir. Bagus Budiwantoro; Dr. Andri Andriyana, GALANDRA
Indonesia‟s wealth of natural resources are not coupled by capabilities to make them fully cultivated, in this case rubber for instance. Huge dependancy of rubber product in industrial process and as a mechanical component demand more in-depth research about rubber in Indonesia. This research is further step of previous research on stress-strain testing for the PT Cipta Daya Mandiriinsani Indonesia‟s rubber industry with NR and NBR types at strain rate 0,1/s and 0,01/s. This study aims to find the appropriate hyperelastic model, governing equation of viscoelastic constitutive model, and simple model of stress relaxation fenomena as one of characteristics of viscoelastic properties of rubber using spring-dashpot analogy. The selected hyperelastic constitutive physically-based models are Arruda-Boyce (8-chain), Yeoh(term 1,2,3), and Ogden(term 1,2,3). Then, stress relaxation is described by stress-strain curve using Maxwell, Standard Linear Solid, and Generalized Maxwell model. Based on experimental data, the coefficients for each model were calculated and used to describe the condition of stress strain relationship for each type of rubber. Comparison for the best fit of the models is performed by calculating error values. For the case of PT Cipta Daya Mandiriinsani Indonesia‟s rubber, Ogden Term 2 model sound to be the best to describe hyperelastic stress strain characteristics, viscoelastic constitutive model works not quite well but development will keep goes on, and stress relaxation fenomena quite well be representated by Generalized Maxwell Model.